Enhanced Organic Carbon Burial in Sediments of Oxygen Minimum Zones Upon Ocean Deoxygenation - Ruvalcaba Baroni, Itzel; Palastanga, Virginia; Slomp, Caroline P. (Frontiers in Marine Science, 2020)
Oxygen minimum zones (OMZs) in the ocean are expanding. This expansion is attributed to global warming and may continue over the next 10 to 100 kyrs due to multiple climate CO$_\text{2}$-driven factors. The expansion of oxygen-deficient waters has the potential to enhance organic carbon burial in marine sediments, thereby providing a negative feedback on global warming. Here, we study the response of dissolved oxygen in the ocean to increased phosphorus and iron inputs due to CO$_\text{2}$-driven enhanced weathering and increased dust emissions, respectively. We use an ocean biogeochemical model coupled to a general ocean circulation model (the Hamburg Oceanic Carbon Cycle model, HAMOCC 2.0) to assess the impact of such regional deoxygenation on organic carbon burial in the modern ocean on time scales of up to 200~kyrs. We find that an increase in input of phosphorus and iron leads to an expansion of the area of the OMZ impinging on continental margin sediments and a significant decline in bottom water oxygen in the open ocean relative to pre-industrial conditions. The associated increase in organic carbon burial could contribute to the drawdown of $\sim$1600~Gt of carbon, which is equivalent to the total amount of CO$_\text{2}$ in the atmosphere predicted for the year 2100 in a business as usual scenario, on time scales of up to 50 kyrs. The corresponding areal extent of sediments overlain by bottom waters with little or no oxygen as estimated by the model is not very different from the minimum area estimated for two major oceanic anoxic events in Earth's past. Such events were associated with major perturbations of the oceanic carbon cycle, including high rates of organic carbon burial. We conclude that organic carbon burial in low oxygen areas in the ocean could contribute to removal of anthropogenic CO$_\text{2}$ from the atmosphere on long time scales.